Comparative Study of Fundamental Movement Skills in Iranian Children and Selected Countries of the World: A Cross-Sectional Study - Sayed Kavos Salehi; Majid Kashef (Vesnu Publications, 2021)
Introduction: This study was performed to compare the fundamental motor skills of children in Iran and selected countries.Materials and Methods: In order to make a cross-cultural comparison regarding the motor development of children in the world, four studies from Iran, United States of America (USA), Portugal, and China were included, in which the test of gross motor development-second edition (TGMD-2) was used. After confirming the inclusion criteria and selecting the final studies, the average percentage of children in each region (country/state/island) who had mastered in fundamental motor skills was extracted, compared, and analyzed. Descriptive statistics, chi-square test, Cramer's V statistics, and ratio were used to analyze the data.Results: There was a relationship between the physical education curriculum guidelines in each country and the number of children who were master in fundamental motor skills in that country. American children's average level of mastery was more than Chinese (P = 0.009), Portuguese (P = 0.005), and Iranian (P = 0.001) children. Besides, no relationship was found between the most popular sport in each country and mastery of fundamental motor skills related to that sport in the studies (Z < 1.645).Conclusion: Apparently, the mere existence of a popular sport in a country does not provide the basis for mastering the skills related to that sport; rather, present findings emphasized the need to appropriate, curriculum-based guidance and instructional components along with opportunities and incentives to develop and master basic motor skills.